Nation within : the history of the American occupation of Hawai'i - Coffman, Tom (Duke University Press, 2016)
Nation Within is the complex history of the events between the overthrow of the Kingdom of Hawaii in 1893 and its annexation to the United States in 1898. Highlighting the native Hawaiians' resistance during that five year span, Tom Coffman shows why occupying Hawaii was crucial to American imperial ambitions.